Chemically based transmissible ER stress protocols are unsuitable to study cell-to-cell UPR transmission. Issue 20 (29th October 2020) - Bignon, Yohan; Poindessous, Virginie; Rampoldi, Luca; Haldys, Violette; Pallet, Nicolas
Abstract : Renal epithelial cells regulate the destructive activity of macrophages and participate in the progression of kidney diseases. Critically, the Unfolded Protein Response (UPR), which is activated in renal epithelial cells in the course of kidney injury, is required for the optimal differentiation and activation of macrophages. Given that macrophages are key regulators of renal inflammation and fibrosis, we suppose that the identification of mediators that are released by renal epithelial cells under Endoplasmic Reticulum (ER) stress and transmitted to macrophages is a critical issue to address. Signals leading to a paracrine transmission of ER stress (TERS) from a donor cell to a recipient cells could be of paramount importance to understand how ER-stressed cells shape the immune microenvironment. Critically, the vast majority of studies that have examined TERS used thaspigargin as an inducer of ER stress in donor cells in cellular models. By using multiple sources of ER stress, we evaluated if human renal epithelial cells undergoing ER stress can transmit the UPR to human monocyte-derived macrophages and if such TERS can modulate the inflammatory profiles of these cells. Our results indicate that carry-over of thapsigargin is a confounding factor in chemically based TERS protocols classically used to induce ER Stress in donor cells. Hence, such protocols are not suitable to study the TERS phenomenon and to identify its mediators. In addition, the absence of TERS transmission in more physiological models of ER stress indicates that cell-to-cell UPR transmission is not a universal feature in cultured cells.